Rapid tremor frequency assessment with the iPhone accelerometer. - Joundi, R; Brittain, J; Jenkinson, N; Green, A; Aziz, T (2011)
The physician is often seeking more efficient ways of performing patient assessments. Currently, measuring tremor frequency requires expensive and bulky equipment. We propose the use of the in-built accelerometer of the iPhone via the iSeismo application for rapid measurement of tremor frequency. We use this device in a series of 7 different tremor cases, and show that the frequency measurements on the iSeismo graph closely match the more sophisticated EMG analysis during tremor. This is a preliminary confirmation of the usefulness of this device in the clinical setting for quick assessment of the dominant frequency component in a variety of tremors.